Advances in improvement of quality and resistance in a multipurpose crop: sea buckthorn. (June 2013) - Ruan, Cheng-Jiang; Rumpunen, Kimmo; Nybom, Hilde
<x xml:space="preserve">Abstract</x> Sea buckthorn is a berry crop with multiple uses. The berries are highly appreciated for their unique taste but are also very rich in bioactive compounds with powerful nutritional and medicinal values. In addition, the plants grow well under adverse conditions, and are often used to fight soil erosion. Utilization of sea buckthorn has therefore increased around the world but serious problems have, nevertheless, been encountered due to drought, salinity, diseases and insect pests. This review covers important aspects of sea buckthorn research, such as heritable and environmentally induced variation in biochemical compounds, causes and effects of the devastating dried-shrink disease, susceptibility to insect pests, methods for conventional breeding, and the utilization of DNA markers for taxonomical and population genetic analyses, and for investigating the inheritance of quality and resistance traits. We also present possibilities to implement innovative biotechnological breeding methods, especially metabolite profiling and MAS/GRC-based markers, for fast and efficient development of elite genotypes with specific nutritional- and health-related bioactive compounds and strong resistance to biotic and abiotic stress.